PRINSIP-PRINSIP SPIRITUAL DALAM KEPEMIMPINAN HINDU - Ni Luh Gede Hadriani (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2020)
The living conditions of Indonesian politics today are still far from what we expect, which is healthy politics. A healthy politics is based on honesty, openness, discipline and always obey the existing regulations, however in reality there are still political organizations which run their organizations undisciplined and violate the rules, albeit this political organization will spawn national leaders. To emphasize that a leader has noble characteristic, a leader must apply the spiritual principles of leadership in Hinduism. Leaders who prioritize these principles will prioritize creativity, initiative, work and a sense of the main nature, so that a leader is able to lead by inspiring, awakening, arousing and inviting so that people feel safe and protected. Thus, prosperity and happiness of the community could be realized. At this time, we need to carry out this spiritual leadership model in the midst of waning community trust in leaders.